PENGARUH MEDIA SOSIAL TERHADAP PENINGKATAN KESADARAN KEWIRAUSAHAAN DI KALANGAN GENERASI Z KABUPATEN ROKAN HULU - Nofriser; Hermansyah (Jurnal Bina Wira, 2024)
This study aims to explore the role of social media in increasing entrepreneurial awareness among Generation Z in Rokan Hulu Regency. In the increasingly advanced digital era, social media has become an important platform that influences various aspects of life, including entrepreneurship. Generation Z, as a generation that has grown up with digital technology, has extensive access to entrepreneurial information and inspiration through social media. This research uses a quantitative approach with a survey method to collect data from 150 Generation Z respondents in Rokan Hulu Regency. Data were analyzed using descriptive and inferential statistical analysis techniques. The results showed that social media has a significant role in increasing entrepreneurial awareness among Generation Z. Sosial media platforms such as Instagram, Facebook and TikTok contribute to disseminating informationl about business opportunities, inspiring business ideas, and providing a space for networking and sharing experiences with fellow entrepreneurs. In addition, social media also plays a role in building positive perceptions of entrepreneurship, which in turn increases the interest and intention for entrepreneurship among Generation Z. Therefore, stakeholders, including the government and educational institutions, are expected to utilize the potential of social media to encourage entrepreneurship growth in the region